An empirical network study of the antimalarial supply chain in Ghana - Osman Adams; Chia-Lin Wang; Edmund Chattoe-Brown; Heather Hamill; Katherine Hampshire; Simon Mariwah; Daniel Amoako-Sakyi; Fiifi Amoako Johnson; Graeme J. Ackland (PLoS ONE, 2026)
A survey of a sample of Ghanaian pharmacies was undertaken to trace the antimalarial drug supply chain. We sampled antimalarial drug outlets in 6 districts across Ghana and traced their immediate suppliers. A third level of the supply chain was obtained by visiting these intermediate suppliers and finding who supplied them. This proved sufficient to track the supply of antimalarial drugs to major manufacturers or importers. We then used techniques of network analysis to study features of the supply chain. By mapping the network to a real geography we demonstrate that the network has a hub and spoke structure, and is dominated by companies in Accra, with a secondary hub in Kumasi. Regional centres such as Tamale and Cape Coast are of lesser significance. We used a range of network measures to analyse the network data provided by the survey. Degree distribution analysis suggests that one company, which appears to deliver direct to many customers, has a particularly dominant position in the network. However, PageRank analysis identifies a different company as being more influential. This company uses a different supply model, via intermediaries, which means that it has fewer direct links to retailers. Mathematical analysis reveals that the distribution network (defined by in-degree distribution over nodes) is scale free (Pareto-type), a characteristic of an unregulated free market for sellers. By contrast, the purchasing network (defined by out-degree distribution) appears to be more log-normal, showing limited agency for individual buyers. It is interesting that a single mathematical measure can capture the different challenges faced by sellers and buyers. Understanding the structure of Ghana’s private antimalarial supply chain provides crucial insights for strengthening medicine distribution systems in other low and middle income countries. Mapping such networks can inform global strategies to improve equitable access and ensure medicine quality.